2019
DOI: 10.1177/0363546519863349
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Unsuccessful Nonoperative Management of Capitellar Osteochondritis Dissecans

Abstract: Background: Osteochondritis dissecans of the humeral capitellum (capitellar OCD) is a common injury among adolescent throwing athletes. Some younger patients with incomplete maturity of the epiphysis and early-stage capitellar OCD are good candidates for nonoperative treatment. However, during initial examination, predicting the need for surgical treatment in patients with capitellar OCD is difficult. Purpose: To perform multivariate ordered logistic regression analysis of data obtained from patients’ medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Recently, the predictors of failure in the nonoperative management of capitellar OCD have been discussed. 4,8,16 Indeed, Takahara et al 16 and Matsuura et al 8 reported that youth patients with incomplete maturity of the epiphysis and early-stage capitellar OCD are good candidates for nonoperative treatment. In agreement with these previous studies, 8,16 we found a relationship between successful OCD rehabilitation and OCD classification: there was a 4-fold greater success rate for early-stage capitellar OCD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, the predictors of failure in the nonoperative management of capitellar OCD have been discussed. 4,8,16 Indeed, Takahara et al 16 and Matsuura et al 8 reported that youth patients with incomplete maturity of the epiphysis and early-stage capitellar OCD are good candidates for nonoperative treatment. In agreement with these previous studies, 8,16 we found a relationship between successful OCD rehabilitation and OCD classification: there was a 4-fold greater success rate for early-stage capitellar OCD.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these previous studies, 8,16 we found a relationship between successful OCD rehabilitation and OCD classification: there was a 4-fold greater success rate for early-stage capitellar OCD. Furthermore, Funakoshi et al 4 showed that preoperative radiographic findings of radial head enlargement and advanced skeletal age of the throwing side compared with that of the nonthrowing side were predictors of advanced-stage capitellar OCD. Moreover, this study found that radiocapitellar congruity was important to the success of nonoperative management for capitellar OCD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with prior data suggesting that patients with open physes or those who are younger have better outcomes with operative and nonoperative management. 3,9,15,19,20 We observed significant improvements in ROM in flexion, extension, and arc of elbow motion in this cohort, without difference with respect to surgical technique or sporting activities. Prior authors have also demonstrated improvements in flexion and/or extension ROM.…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 53%